Factors contributing to customers' satisfaction towards online banking in Sungai Petani / Mohamad Zahrul Asyiq Zuraidi and Ahsan Zikri Sarkawi - Zuraidi, Mohamad Zahrul Asyiq; Sarkawi, Ahsan Zikri (2018)
this chapter, it covers about the introduction of the research and it also provides universal explanation and framework of the research flow. In this research, it mainly focusing and looking at on factor adding pleasant to customers towards online banking. The area will look at about the background of study, problem statement, research objective and question, significance of the study and summary of the first chapter.